2020
DOI: 10.1155/2020/3569125
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation of Biohydrocarbon Fuel by Catalytic Hydrogenation of Swida wilsoniana Pyrolysis Products

Abstract: The Ni-ZSM-5 catalyst, under four different factors of Swida wilsoniana pyrolysis products of catalytic hydrogenation, GC-MS, FI-IR, and elemental analyzers, was used to identify the elements, carbon chain distribution, and composition of the products. The effects of reaction temperature, reaction pressure, and catalyst hydrogenation level on the conversion rate were investigated. The reaction pressure and the amount of catalyst are the main factors that affect the conversion of the pyrolysis products into bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Its oil is rich in unsaturated fatty acids, vitamin E, β-carotene, and other functional ingredients, which not only have hypolipidemic function, but also help to supply essential fatty acids and prevent fatty liver and atherosclerosis [ 45 , 46 ]. In addition, studies have shown that the Swida wilsoniana oil could be catalyzed to produce high-quality biofuels, which can be used as an alternative energy source with less competition with foods [ 47 , 48 ].…”
Section: Woody Oil Plant Resources In Chinamentioning
confidence: 99%
“…Its oil is rich in unsaturated fatty acids, vitamin E, β-carotene, and other functional ingredients, which not only have hypolipidemic function, but also help to supply essential fatty acids and prevent fatty liver and atherosclerosis [ 45 , 46 ]. In addition, studies have shown that the Swida wilsoniana oil could be catalyzed to produce high-quality biofuels, which can be used as an alternative energy source with less competition with foods [ 47 , 48 ].…”
Section: Woody Oil Plant Resources In Chinamentioning
confidence: 99%